Quality of disclosed information with emphasis on goodwill impairment - Markéta Boučková (European Financial and Accounting Journal, 2016)
This paper focuses on an analysis of the mandatory disclosure of goodwill impairment information in compliance with the international accounting standard IAS 36. The international financial reporting standards require a wide range of disclosed information concerning the goodwill impairment such as the carrying amount of goodwill allocated to the cash generating unit, determination of the discount rate applied to areas such as cash flow projections or sensitivity analysis. Prior research on disclosure requirements of goodwill impairment has shown generally low level of compliance within the selected companies. The main goal of this paper is to find out whether companies with higher goodwill intensity disclose the information required by IFRS on the impairment of goodwill. An empirical approach consisted of analysing consolidated financial statements of selected companies listed on DAX 30 and FTSE 100 . Our sample covered 89 companies and focused on their statements from 2010 to 2013. The results showed generally low compliance that subsequently affected the comparability of statements. The following requirements were identified as critical - determination of growth rate, disclosure of growth rate used to extrapolate cash flow projections, determination of discount rate, discount rates applied to cash flow projections and disclosure of the sensitivity analysis. These findings can be further utilized by regulators in order to increase the quality of disclosures in financial statements.
Keywords: M40; 650; Goodwill; Goodwill impairment; IAS 36; Mandatory disclosure